Blood Levels of Some Toxic Metals and Their Potential Health Impact in Human Immunodeficiency Type 1 Infected Subjects. - Mbonu, I; Abiodun, EM (African Journal of Tropical Medicine and Biomedical Research, 2019)
Background: The introduction of antiretroviral therapy in the management of immunodeficiency virus infection has reduced the mortality rate and increased the average life-expectancy of infected subjects. The prevalence of non-infectious chronic diseases and malignancies are also on the rise. Environmental pollutants could adversely impact on the prognostic outcomes of HIV-1 infection probably due to the combination of the effects of environmental exposures and chronic inflammation and the role of toxic metals exposure and their health impact in infected individuals have been under-reported. Objective: To evaluate the levels of cadmium (Cd),lead (Pb), mercury (Hg) and nickel (Ni) in HIV-1 infected subjects on highly active anti-retroviral therapy(HAART), HAART-naïve and discusses their potential health impacts. Materials and methods: The study participants were 300 made up of 100 confirmed HIV-1 positive on HAART, 100 HIV-1 positive HAART-naïve and 100 HIV-1 negative controls. Measured toxic metal levels were determined using inductively coupled plasma mass spectrometer (Agilent 7500, Norwalk, U.S.A) Results: Data indicated significantly higher (p<0.001) measured toxic metals in HIV positive subjects than controls, with levels in subjects on HAART higher than HAART-naive. Conclusion: High toxic metal levels may lead to increased oxidative stress and adverse prognostic outcomes. Periodic evaluation of toxic metals in HIV-1 infected subjects is suggested and preventive strategies of environmental pollutants should be adopted.